1998
DOI: 10.1095/biolreprod59.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages, Cell Proliferation, and Cell Death in the Human Menstrual Corpus Luteum1

Abstract: We studied the presence and numbers of macrophages in the different compartments of the human menstrual corpus luteum (CL) in relation to the proliferative activity and apoptosis in luteal cells. Macrophages were recognized by immunohistochemical demonstration of the lysosome-associated glycoprotein CD68, and proliferating cells by immunohistochemical detection of the cell cycle-related protein Ki67 and by counting mitotic cells. In general, changes in the number of macrophages were parallel to the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 31 publications
5
54
0
1
Order By: Relevance
“…DNA ladder formation and apoptotic cells are detected in the mid-luteal phase corpus luteum and apparently increase in the regressing corpus luteum, whereas they are not detected in the corpus luteum of pregnancy [47][48][49]. It is generally agreed that apoptotic cells remarkably increase in number in the corpus luteum during the late luteal phase [50,51]. On the other hand, Fraser et al [52] report that autophagocytosis may be a main mechanism for natural structural luteolysis rather than apoptosis in primates because electron microscopic analysis revealed that natural luteolysis was associated with luteal cell atrophy, condensation of cytoplasmic inclusions and organelles and accumulation of lipids, but was not associated with the ultrastructural criteria for apoptosis in marmosets.…”
Section: Humansmentioning
confidence: 99%
“…DNA ladder formation and apoptotic cells are detected in the mid-luteal phase corpus luteum and apparently increase in the regressing corpus luteum, whereas they are not detected in the corpus luteum of pregnancy [47][48][49]. It is generally agreed that apoptotic cells remarkably increase in number in the corpus luteum during the late luteal phase [50,51]. On the other hand, Fraser et al [52] report that autophagocytosis may be a main mechanism for natural structural luteolysis rather than apoptosis in primates because electron microscopic analysis revealed that natural luteolysis was associated with luteal cell atrophy, condensation of cytoplasmic inclusions and organelles and accumulation of lipids, but was not associated with the ultrastructural criteria for apoptosis in marmosets.…”
Section: Humansmentioning
confidence: 99%
“…Hyporesponders, also exhibited a lower concentration of IL-1β and VEGF in the culture supernatants, compared to hyper-responder patients, emphasizing that in hyporesponders the primary function of macrophages is to eliminate the apoptotic bodies, as was previously reported [9,10]. In a recent article by Balasch et al [4] it was shown that macrophages do release VEGF, but whether these macrophages are able to release cytokines while they are phagocytosing is still a matter of controversy.…”
Section: Discussionmentioning
confidence: 88%
“…Also, ovarian macrophages use phagocytosis to remove apoptotic granulosa cells and apoptotic luteal cells [9,10], thereby contributing to the processes of follicular atresia and luteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are major secretory cells capable of releasing cytokines, chemokines and growth factors that function in normal, inflammatory and disease processes of most tissues [10]. CD68 positive cells are localized in human ovaries primarily to the vascular connective tissue and theca-lutein areas of the corpus luteum, although some are found in the granulose-lutein cell layer [11]. After ischemia reperfusion, impaired ovarian tissue melatonin effect was characterized by vascular injury and inflammation and the prevention of CD31 and CD68 markers.…”
Section: Introductionmentioning
confidence: 99%